Políticas de precificação do setor de saneamento urbano no Brasil: as evidências do equilíbrio de baixo nível - Faria, Ricardo Coelho de; Nogueira, Jorge Madeira; Mueller, Bernardo (Estudos Econômicos (São Paulo), 2005)
The existence of a low level equilibrium balance in the supply of urban sewage services is analysed in this essay. The low level equilibrium hypothesis is related to the model by Spiller e Savedoff (1999) for Latin American countries. In their view, government opportunism and populism lead towards prices below costs of providing sewage service in developing countries. This is the starting point of a vicious circle, leading towards low quality of public utility services. Like other countries in Latin America, data for Brazil demonstrate that, with few exceptions, the low level equilibrium of water and sewage supply services in urban areas. However, some particularities in the Brazilian reality suggest that this low level equilibrium may be explained in economic terms. It is shown that wealthier states and municipalities provide high quality services, regardless of the regulatory system.